Characterization of a novel GH10 alkali‑thermostable xylanase from a termite microbiome - Mon, Maria Laura (2022)
The aim of the present study was to assess the biochemical and molecular structural characteristics of a novel alkali-thermostable GH10 xylanase (Xyl10B) identified in a termite gut microbiome by a shotgun metagenomic approach. This endoxylanase candidate was amplified, cloned, heterologously expressed in Escherichia coli and purified. The recombinant enzyme was active at a broad range of temperatures (37–60 ºC) and pH values (4–10), with optimal activity at 50 ºC and pH 9. Moreover, its activity remained at more than 80% of its maximum at 50 °C for 8 h. In addition, Xyl10B was found to be stable in the presence of salt and several ions and chemical reagents frequently used in the industry. These characteristics make this enzyme an interesting candidate for pulp and paper bleaching industries, since this process requires enzymes without cellulase activity and resistant to high temperatures and alkaline pH (thermo-alkaliphilic enzymes). The products of xylan hydrolysis by Xyl10B (short xylooligosaccharides, xylose and xylobiose) could be suitable for application as prebiotics and in the production of bioethanol.